2006
DOI: 10.1073/pnas.0602627103
|View full text |Cite
|
Sign up to set email alerts
|

Ansa-metallocene polymerization catalysts derived from [2+2]cycloaddition reactions of bis(1-methylethenyl-cyclopentadienyl)zirconium systems

Abstract: Bis(1-methylethenyl-cyclopentadienyl)zirconium dichloride (7a) was prepared by a fulvene route. Photolysis at 0°C with Pyrexfiltered UV light resulted in a rapid and complete intramolecular [2؉2]cycloaddition reaction to yield the corresponding cyclobutylene-bridged ansa-zirconocene dichloride isomer (8a). This is one of the rare examples of an organic functional group chemistry that leads to carbon-carbon coupling at the framework of an intact sensitive group 4 bent metallocene complex. More sterically hinder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 38 publications
(26 reference statements)
2
8
0
2
Order By: Relevance
“…This study has shown that the parent bis(vinyl-Cp)zirconium dichloride complex ( 6 ) readily undergoes a photochemically induced intramolecular [2+2] cycloaddition reaction under our typical reaction conditions. This observation follows the general trend for this reaction type, as we have seen recently , that the outcome of this organometallic photocycloaddition is strongly dependent on the size and steric bulk of the α-substituent at the alkenyl unit. It seems to be a rule that small substituents (H, CH 3 ) at this position lead to a photostationary equilibrium that lies completely on the side of the ansa -metallocene isomer, whereas large cycloalkyl or aryl substituents may shift this equilibrium substantially, so that in these cases we often find mixtures of the open and ansa -metallocene isomers.…”
Section: Some Conclusionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study has shown that the parent bis(vinyl-Cp)zirconium dichloride complex ( 6 ) readily undergoes a photochemically induced intramolecular [2+2] cycloaddition reaction under our typical reaction conditions. This observation follows the general trend for this reaction type, as we have seen recently , that the outcome of this organometallic photocycloaddition is strongly dependent on the size and steric bulk of the α-substituent at the alkenyl unit. It seems to be a rule that small substituents (H, CH 3 ) at this position lead to a photostationary equilibrium that lies completely on the side of the ansa -metallocene isomer, whereas large cycloalkyl or aryl substituents may shift this equilibrium substantially, so that in these cases we often find mixtures of the open and ansa -metallocene isomers.…”
Section: Some Conclusionsupporting
confidence: 88%
“…cycloalkyl, aryl) resulted in photostationary equilibria that sometimes lay far on the side of the open starting materials (see Scheme ) . For us the introduction of the easily prepared Cp-C(CH 3 )CH 2 ligands marked a turning point: attachment of the small methyl substituent at the Cp-conjugated alkenyl moiety resulted in complete conversions to the respective ansa -zirconocene by intramolecular photochemical [2+2] cycloaddition reaction under simple and straightforward experimental conditions . This has made the [2+2] cycloaddition a suitable and reliable method for ansa -zirconocene synthesis …”
Section: Introductionmentioning
confidence: 99%
“…Oft ist es wegen der Empfindlichkeit der metallhaltigen Verbindungen schwierig, an metallorganischen Gerüsten Umwandlungen typischer organischer funktioneller Gruppen durchzuführen. Dies gilt besonders für viele metallorganische Verbindungen “früher” Übergangsmetalle, bei denen erst in jüngster Zeit eine größere Zahl geeigneter Verfahren für solche Transformationen beschrieben wurde 61be. 83 Metallfreie katalytische Hydrierungen mit frustrierten Lewis‐Paaren gehören zu diesen hinreichend milden Methoden.…”
Section: Anwendungen In Der Metallorganischen Chemieunclassified
“…Das Ansa ‐ Metallocen 133 ist durch eine säurekatalysierte intramolekulare Mannich‐Reaktion leicht aus dem entsprechenden zweifach Enamino‐substituierten Zirconocen zugänglich 61be. Im analogen [3]Ferrocenophan 120 eröffnete die nachfolgende Hydrierung beider Doppelbindungen einen Zugang zu einer Reihe nützlicher Liganden für die asymmetrische Katalyse 62.…”
Section: Anwendungen In Der Metallorganischen Chemieunclassified
“…This reaction type proved to be somewhat substituent-sensitive but use of a proper substitution pattern at the alkenyl groups allowed very efficient ansa-metallocene formation by the photochemical [2+2] cycloaddition route. [7][8][9][10][11][12] Photolysis of bis(butadienyl-Cp)ZrCl 2 systems takes a similar route. At ambient temperature this reaction rapidly and selectively leads to the formation of the isomeric cyclooctadienylene-bridged ansa-metallocenes by formal [4+4] cycloaddition.…”
Section: Introductionmentioning
confidence: 93%